Solar-driven CO2 conversion to methane and methanol using different nanostructured Cu2O-based catalysts modified with Au nanoparticles - Perini, João Angelo Lima [UNESP]; Torquato, Lilian D. Moura [UNESP]; Brito, Juliana F. de [UNESP]; Andolpho, Gustavo A.; Gonçalves, Mateus A.; De Angelis, Leonardo D.; Germano, Lucas D.; Córdoba de Torresi, Susana I.; Ramalho, Teodorico C.; Zanoni, Maria V. Boldrin [UNESP] (Elsevier, 2024)
This work describes the use of TiO2 nanotubes-based electrodes (TNT) modified with Cu2O nanostructures and gold nanoparticles for the photoelectroreduction of CO2 to produce value-added compounds. A thin layer of polydopamine was used as both an adherent agent and an electron transfer mediator, due to its π-conjugated electron system. The highest production yield was achieved using a TNT@PDA/Nc/Au40% electrode, with Faradaic efficiencies of 47.4% (110.5 μM cm−2) and 27.8% (50.4 μM cm−2) for methanol and methane, respectively. The performance of the photoelectrodes was shown to be Cu2O facet-dependent, with cubic structures leading to greater conversion of CO2 to methanol (43%) and methane (27%), compared to the octahedral morphology, while a higher percentage of metallic gold on the nanostructured Cu2O surface was mainly important for CH4 production. Density functional theory (DFT) calculations supported these findings, attributing the superior photoelectrocatalytic performance of the TNT@PDA/Nc/Au40% electrode for CH4 generation to the formation of an OCH3 intermediate bonded to Au atoms. Studies using isotope-labeling and analysis by gas chromatograph-mass (GC-MS) demonstrated that 13CO2 was the source for photoelectrocatalytic generation of 13CH3OH and 13CH313CH2OH.
Keywords: CO2 photoelectroreduction; Cu2O nanocubes; DFT calculations; Photoelectrocatalysis; Polydopamine